THE ROLE OF HEALTH INFORMATION SYSTEM IN MATERNAL AND CHILD HEALTHCARE SERVICES - Chowdhury, Rakhi; Kumari, Leena; Panda, Subhamay (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Health information system deals with any system that helps in capturing, storing, transmitting, and managing health-related information of an individual or to demonstrate the activities or organizations working within health-care sector. In the developing countries, maternal and child health is gaining concern due to increasing cases of morbidity and mortality. The disparities among the maternal, infant, and child health are a growing concern in India and are governed by various determinants such as socioeconomic status, literacy, quality of health care, discrimination, and biological and genetic factors. Accurate and reliable health information and data are the basis for decision-making across the health-care sector and are crucial for the development and implementation of health system policy by the policy-makers. Strict monitoring and evaluation of the present program design and its implementation is required at the microlevel to effectively utilize the resources for the improvement of maternal and child health. Our present article focuses on evaluating the coverage gap at the different levels for the provision of health-care facilities to maternal, neonatal, and child health, immunization, and treatment of poor children. Big data plays a major role in providing sound and reliable health-related information and also help in managing and recording structured and unstructured data. More concrete plans are required further to reduce the inequalities in health-care interventions for providing better maternal and child health-care services in our nation.